2010
DOI: 10.1002/etc.359
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of temperature and a herbicide mixture on the soft‐shell clam Mya arenaria (Mollusca, Bivalvia)

Abstract: Abstract-The aim of the current study was to investigate effects of temperature and a mixture of herbicides on the physiological status of the bivalve Mya arenaria. Bivalves acclimated to two temperatures (7 and 188C) were exposed for 28 d to 0.01 mg/L of a pesticide formulation containing dichlorophenoxyacetic acid (2,4-D), 2-(2-methyl-4-chlorophenoxy) propionic acid (mecoprop), and 3,6-dichloro-2-methoxybenzoic acid (dicamba). At days 7, 14, and 28, mortality, immune parameters (hemocyte number, phagocytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 35 publications
(46 reference statements)
2
11
0
1
Order By: Relevance
“…Other in vitro models from marine invertebrates have also been used in marine ecotoxicological studies: oyster embryos (Galgani et al 2009;Mamindy-Pajany et al 2011), sponge primmorphs (Châtel et al 2011) and isolated invertebrate haemocytes (Anderson et al 1997;Cima et al 2004Cima et al , 2008Gopalakrishnan et al 2011;Greco et al 2011). In haemocytes, the study of pollutant effects demonstrated an alteration of parameters such as cell viability, phagocytotic activity, esterase activity or production of reactive oxygen species (Cima et al 2004;Gagnaire et al 2006;Gopalakrishnan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro models from marine invertebrates have also been used in marine ecotoxicological studies: oyster embryos (Galgani et al 2009;Mamindy-Pajany et al 2011), sponge primmorphs (Châtel et al 2011) and isolated invertebrate haemocytes (Anderson et al 1997;Cima et al 2004Cima et al , 2008Gopalakrishnan et al 2011;Greco et al 2011). In haemocytes, the study of pollutant effects demonstrated an alteration of parameters such as cell viability, phagocytotic activity, esterase activity or production of reactive oxygen species (Cima et al 2004;Gagnaire et al 2006;Gopalakrishnan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…shortterm bioassays with one or two test species). As an example, Greco et al (2010) investigating effects of a mixture of herbicides on the physiological status of the soft clam, Mya arenaria, showed that in clams kept at 18°C, pesticides appeared to induce minor effects compared with animals kept at 7°C. They concluded that increased temperature may modify the response of Mya arenaria to pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in adult Pacific cupped oysters revealed that diuron induces partial spawning and atrophy of the digestive epithelium after 1 week of exposure at 1 µg L -1 (Buisson et al, 2008). Greco et al (2010) investigated effects of a mixture of herbicides on the physiological status of the soft clam, Mya arenaria. Clams were exposed for 28 days to 0.01 mg L -1 of a pesticide mixture: dichlorophenoxyacetic acid (2,4-D), 2-(2-methyl-4-chlorophenoxy) propionic acid (mecoprop), and 3,6-dichloro-2-methoxybenzoic acid (dicamba).…”
Section: Other Effects Of Pesticides On Marine Bivalvesmentioning
confidence: 99%
“…M. arenaria is a member of the phylum Mollusca, ranging throughout the northern, boreal coastline spanning several continents [1]. The clam is a filter-feeding bivalve, causing it to bioaccumulate environmental pollutants, and thus acts as a sentinel species [4]. In Maine, M. arenaria is harvested commercially, and, in 2015, the soft-shell clam fishery was the second most important in dockside value ($22.5 million) behind the American lobster, Homarus americanus ($495.4 million) [5].…”
Section: Introductionmentioning
confidence: 99%